Pentraxin 3 Promotes Glioblastoma Progression by Negative Regulating Cells Autophagy - Wang, Zeyu; Wang, Xing; Zhang, Nan; Zhang, Hao; Dai, Ziyu; Zhang, Mingyu; Feng, Songshan; Cheng, Quan (Frontiers in Cell and Developmental Biology, 2020)
Glioblastoma is the most malignancy tumor generated from the central nervous system along with median survival time less than 14.6 months. Pentraxin 3 has been proved its association with patients’ poor survival outcome in various tumor. Recently, several studies revealed its association with glioblastoma progression but the mechanism is remained unknown. Autophagy is a programmed cells death and acts critical role in tumor progression. In this study, pentraxin 3 is recognized as prognostic prediction biomarker of glioblastoma and can promote glioblastoma progression through negative modulating tumor cells autophagy. Transcription factor JUN is assumed to participate in cells autophagy modulation by regulating pentraxin 3 expression. This work reveals novel mechanism of pentraxin 3 mediated glioblastoma progression. Furthermore, JUN is identified as potential transcription factor involves in pentraxin 3 mediated tumor cells autophagy.